A novel bifunctional catalyst for overall water electrolysis: nano IrxMn(1−x)Oy hybrids with L12-IrMn3 phase. Issue 5 (17th December 2021) - Ren, Zhandong; Wang, Yanyan; Jiang, Hucheng; Jiang, Hongwei; Tian, Miaojie; Liu, Ye; Han, Juanjuan; Fang, Hua; Zhu, Yuchan
Abstract : Nano Ir x Mn(1− x ) O y hybrids with L12 -IrMn3 phase as a novel bifunctional catalyst with ultra-low Ir loading for overall water electrolysis in an acidic solution. Abstract : A nano Ir x Mn(1− x ) O y hybrid electrode with a L12 -IrMn3 phase was used as a bifunctional catalyst with ultra-low iridium loading for overall water electrolysis in an acid solution for the first time. The HER activity of the Ir x Mn(1− x ) O y hybrid electrode not only exceeded that of IrO2, but also exceeded that of Pt/C. The OER activity of the Ir x Mn(1− x ) O y hybrid electrode also exceeded that of IrO2 .